(untitled) (Research, Society and Development, 2021)
Introduction: Libidibia Ferrea is a plant with proven therapeutic properties for the prevention and treatment of oral diseases. Objective: To evaluate an orabase source of Libidibia ferrea for cytotoxicity. Methodologys: The hemolysis test was performed using the qualitative assessment method of free hemoglobin and the fibroblast cell culture test using the Alamar Blue method. The stem bark extract, base vehicle, its adjuvants and orabase base were tested. Results: No hemolysis test either the stem bark extract or the above and its components did not dissipate hemolysis when visually evaluating the supernatant from each well. In the Alamar Blue test, it did not show toxicity in any of the tested solutions. Conclusion: Based on the results, the stem bark extract and the orabase base of Libidibia ferrea L. were not toxic when tested in red blood cells and fibroblast cell cultures.